Assessment of a gluten‐free laboratory exercise in an undergraduate food processing course. Issue 4 (10th November 2021) - Herman, Melanie L.; Brown, Janae; Yucel, Umut; Getty, Kelly J. K.
Abstract: There is a growing body of research that suggests better course outcomes for instructors that incorporate active learning into their curriculum. Laboratory exercises can be used to promote active learning. The objective of this study was to develop and assess the efficacy of a gluten‐free bread laboratory exercise for an undergraduate course (Fundamentals of Food Processing). Students enrolled in the course worked in groups to prepare four treatments: 100% white whole grain sorghum as control (C), 15% burgundy waxy sorghum (15W), 25% burgundy waxy sorghum (25W), and 35% burgundy waxy sorghum (35W) in a gluten‐free bread formulation. Students evaluated physical properties (yield, loaf height, color, water activity) using analytical measurements, and organoleptic properties (appearance, color, texture, flavor, and overall acceptability) via sensory analysis on a hedonic scale. Students wrote a scientific report to communicate the results. At the completion of the lab, students answered survey questions ( n = 53 or 85% of the class) to self‐evaluate their understanding of gluten‐free bread properties, research and writing skills, and food processing knowledge. Sixty percent or more of the students said that the exercise improved their understanding of the physical and sensory properties of gluten‐free bread. Over 68% of students agreed or strongly agreed that the exercise reinforced their research and writing skills. Over 75% of respondents felt the exercise improved their food processing knowledge. Overall, the results of the survey indicated that the active lab exercise was effective in teaching the desired learning outcomes.